Réponses

Meilleure réponse !
2014-10-23T12:42:40+02:00
A= (4x+7) -(7x-5)
A= 4x +7 -7x +5
A= -3x +12

B= (-2x+3) + (4x+7)
B= -2x +3 +4x +7
B= 2x +10

C= 4(2x+4) -2(5x+5)
C= 8x +16 -10x -10
C= -2x +6

D= (3x+7) - (2x+3) (4x-5)
D= 3x +7 - (8x² -10x +12x -15)
D= 3x +7 -8x² +10x -12x +15
D= -8x² +x +22
  • Utilisateur Brainly
2014-10-23T14:34:53+02:00
A= (4x + 7) - (7x - 5)
A= 4x + 7 - 7x + 5
A= - 3x + 12

B= (- 2x + 3) + (4x + 7)
B= - 2x + 3 + 4x + 7
B= 2x + 10

C= 4(2x + 4) - 2(5x + 5)
C= 8x + 16 - 10x - 10
C= - 2x + 6

D= (3x + 7) - (2x + 3)(4x - 5)
D= 3x + 7 - (8x² - 10x + 12x - 15)
D= 3x + 7 - 8x² + 10x - 12x + 15
D= - 8x² + x + 22